EXTENDED KALMAN FILTER AS A FULL STATE OBSERVER IN APPLICATION OF THE INERTIA WHEEL PENDULUM - Gośliński, Jarosław; Owczarkowski, Adam (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
This paper presents derivation of the full state observer for an inverted, inertia wheel pendulum (IWP). This is a non-linear, underactuated mechanical system and therefore it has more degrees of freedom than control variables. In order to control this mechanical system properly, knowledge of all state variables is needed. In this paper, authors presented IWP’s model, which was later written in matrix form. Finally, based on the model, full state observer was derived. In the end its results were shown.